2015
DOI: 10.2527/jas.2014-8374
|View full text |Cite
|
Sign up to set email alerts
|

Acetate and glucose incorporation into subcutaneous, intramuscular, and visceral fat of finishing steers1

Abstract: The objectives of this study were to assess the effects of early grain feeding on acetate and glucose turnover rates and acetate and glucose preference for palmitate synthesis by subcutaneous fat (SCF), intramuscular fat (IMF), and visceral fat (VF) in finishing steers. Sixteen Angus × Simmental steers were used in the study; 8 were early weaned (EW) and fed a high-grain diet immediately after weaning for 100 or 148 d, and 8 remained with their dams on pasture until weaning at 202 ± 5 or 253 ± 5 d of age. Norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…However, the overall lack of effect of substituting high-energy supplement for pasture on IMF content during the immediate postweaning period indicates that it did not enhance development and accumulation of intramuscular adipocytes. As in later stages of growth and development, and consistent with the findings of Meteer et al (2013) and Nayananjalie et al (2015), it is likely that total energy supply is more important for adipocyte development and/or adipogenesis within IMF during the immediate postweaning phase than are substrate-specific effects.…”
Section: Discussionsupporting
confidence: 69%
“…However, the overall lack of effect of substituting high-energy supplement for pasture on IMF content during the immediate postweaning period indicates that it did not enhance development and accumulation of intramuscular adipocytes. As in later stages of growth and development, and consistent with the findings of Meteer et al (2013) and Nayananjalie et al (2015), it is likely that total energy supply is more important for adipocyte development and/or adipogenesis within IMF during the immediate postweaning phase than are substrate-specific effects.…”
Section: Discussionsupporting
confidence: 69%
“…As mentioned before, early studies demonstrated that acetate and glucose are the major precursors used for biosynthesis of fatty acids in ruminants, where intramuscular adipocytes prefer glucose, and subcutaneous adipocytes prefer acetate as lipogenic substrates (Smith andCrouse, 1984, May et al, 1995). On the other hand, Nayananjalie et al (2015) detected that acetate is the main precursor for lipid synthesis across fat depots. In addition, according to Choi et al (2014), as cattle become heavier, the contribution of glucose to fat synthesis decreases whereas the use of acetate for fat synthesis increases in intramuscular adipose tissue (Figure 3).…”
Section: Marblingmentioning
confidence: 99%
“…It is the main site of microbial feed digestion and fermentation that produces short-chain fatty acids (SCFAs), which are a major energy source for cattle accounting for up to 80 % of total energy requirements [ 14 , 15 ]. SCFAs are mainly absorbed from the rumen [ 16 ] and metabolized within the rumen epithelium, liver and peripheral tissues to generate energy for use in maintenance, growth and activity [ 17 , 18 ]. Studies have indicated that SCFAs are absorbed by both simple diffusion [ 16 ] and protein-mediated transport through bicarbonate - dependent and - independent mechanisms [ 19 ].…”
Section: Introductionmentioning
confidence: 99%